Beta Adrenergic Regulation of Intrapulmonary Arteriovenous Anastomoses in Intact Rat and Isolated Rat Lungs - Bates, Melissa L.; Jacobson, Joseph E.; Eldridge, Marlowe W. (Frontiers in Physiology, 2017)
Intrapulmonary arteriovenous anastomoses (IPAVA) allow large diameter particles of venous origin to bypass the pulmonary capillary bed and embolize the systemic arterial circulation. IPAVA have been routinely observed in healthy humans with exercise, hypoxia and catecholamine infusion, but the mechanism by which they are recruited is not well-defined. We hypothesized that beta-adrenergic receptor stimulation recruits IPAVA and that receptor blockade would limit hypoxia-induced IPAVA recruitment. To test our hypothesis, we evaluated the transpulmonary passage of microspheres in intact rats and isolated rats lung infused with the beta-adrenergic receptor agonist isoproterenol. We also evaluated IPAVA recruitment in intact rats with hypoxia and the beta-adrenergic receptor blocker propranolol. We found that IPAVA are recruited in the intact rat by isoproterenol and their recruitment by hypoxia can be minimized by propranolol, suggesting a role for the adrenergic system in the recruitment of IPAVA by hypoxia. IPAVA recruitment is completely abolished by ventilation with 100% oxygen. Isoproterenol also recruits IPAVA in isolated rat lungs. The fact that isoproterenol can recruit IPAVA in isolated lungs, without increased pulmonary flow, suggests that elevated cardiac output is not required for IPAVA recruitment.